Leptolejeunea nigra (Lejeuneaceae), a new species with brownish black ocelli based upon morphology and DNA sequences - Shu, Lei; Zhu, Rui-Liang (Phytotaxa, 2019)
Based on molecular phylogenetic analyses and morphological characters, a new species from Bangladesh, northern Vietnam, and southwestern China, Leptolejeunea nigra, is described. It is mostly similar to L. balansae but remarkable for having brownish black ocelli in its leaf lobes. In the molecular phylogeny, the samples of L. nigra are not nested within any clade and form an independent lineage. In particular, the molecular dating suggested that the divergence of L. nigra happened in time span of the formation of the Himalayas.